Importance of Reciprocal Balance of T Cell Immunity in Mycobacterium abscessus Complex Lung Disease - Kim, Su-Young; Koh, Won-Jung; Kim, Yee Hyung; Jeong, Byeong-Ho; Park, Hye Yun; Jeon, Kyeongman; Kim, Jong-Seok; Cho, Sang-Nae; Shin, Sung Jae (PloS one, 2014)
Little is known about the nature of the host immune response to Mycobacterium abscessus complex (MABC) infection. The aim of the present study was to investigate whether alterations in serum immunomolecule levels after treating MABC lung disease patients with antibiotics can reflect the disease-associated characteristics. A total of 22 immunomolecules in 24 MABC lung disease patients before and after antibiotic therapy were quantitatively analyzed using a multiplex bead-based system. In general, the pre-treatment levels of T helper type 1 (Th1)-related cytokines, i.e., interferon (IFN)-γ and interleukin (IL)-12, and Th2-related cytokines, i.e., IL-4 and IL-13, were significantly decreased in patients compared with control subjects. In contrast, the pre-treatment levels of Th17-related cytokines, i.e., IL-17 and IL-23, were significantly increased in MABC patients. Interestingly, significantly higher levels of IFN-γ-induced protein (IP)-10 and monokine induced by IFN-γ protein (MIG) were detected in patients with failure of sputum conversion at post-treatment compared to patients with successful sputum conversion. Reduced Th1 and Th2 responses and enhanced Th17 responses in patients may perpetuate MABC lung disease, and the immunomolecules IP-10 and MIG, induced through IFN-γ, may serve as key markers for indicating the treatment outcome.